The young and the digital : what the migration to social-network sites, games, and anytime, anywhere media means for our future - Watkins, S. Craig (Samuel Craig) (Boston : Beacon Press, 2009)
In this book, the author, a media expert explains how and why the digital migration is transforming youth culture, identity, and everyday life. He draws from more than 500 surveys and 350 in depth interviews with young people, parents, and educators to understand how a digital lifestyle is affecting the ways youth learn, play, bond, and communicate. The book covers the influence of MySpace and Facebook, the growing appetite for "anytime, anywhere" media and "fast entertainment," how online "digital gates" reinforce race and class divisions, and how technology is transforming America's classrooms. He also debunks popular myths surrounding cyberpredators, Internet addiction, and social isolation. The result is a portrait, both celebratory and wary, about the coming of age of the first fully wired generation.
Introduction: The young and the digital -- Digital migration : young people's historic move to the online world -- Social media 101 : what schools are learning about themselves and young technology users -- The very well connected : friending, bonding, and community in the digital age -- Digital gates : how race and class distinctions are shaping the digital world -- We play : the allure of social games, synthetic worlds, and second lives -- Hooked : rethinking the internet addiction debate -- Now! Fast entertainment and multitasking in an always-on world -- "May I have your attention?" : the consequences of anytime, anywhere technology -- Conclusion: A message from Barack : what the young and the digital means for our political future.
Includes bibliographical references (p. 219-241) and index.
Keywords: Mass media and youth -- United States; Technology and youth -- United States; Digital media -- Social aspects -- United States; Teenagers -- Social networks -- United States; Internet -- Social aspects; Online social networks -- United States